Factors associated with presenteeism in nursing workers - Bruno da Silva Santos; Fernanda Ludmilla Rossi Rocha; Juliano Bortolini; Fábio de Souza Terra; Marília Duarte Valim
ABSTRACT Objective: to analyze factors associated with presenteeism in nursing workers with sociodemographic variables, health and work conditions, productivity and musculoskeletal symptoms. Methods: this is a cross-sectional, descriptive and analytical study, with 306 nursing workers from a hospital and municipal emergency room in a Brazilian capital. The Stanford Presenteeism Scale, the Work Limitations Questionnaire, the Nordic Musculoskeletal Questionnaire and a demographic questionnaire on nursing professionals' working conditions and health were used. Bivariate and multivariate analyzes were performed, respecting a significance level of 5%. Results: presenteeism was found in 43.8% of professionals and significant associations with CLT work (p=0.002), workplace - Intensive Care Units (p=0.008), physical exercise twice a week (p=0.008), presence of musculoskeletal symptoms, with low back pain being representative (p=0.001). The productivity loss was 8.8. Conclusions: the study confirms a high rate of presenteeism among nursing workers.